Recombination between two integrated proviruses, one of which was inserted near c-myc in a retrovirus-induced rat thymoma: implications for tumor progression. - Lazo, P A (1988)
Of 17 Moloney murine leukemia virus (MoMuLV)-induced rat thymomas, 2 contained rearrangements in c-myc. In one of these tumors the observed rearrangement was not due to the insertion of an intact MoMuLV provirus. The rearranged c-myc DNA fragment from this thymoma was cloned and examined by restriction endonuclease mapping, hybridization to MoMuLV proviral DNA probes, and DNA sequence analysis. These analyses revealed that the c-myc rearrangement in this tumor was due to the presence of a partially duplicated MoMuLV long terminal repeat (LTR) 5' to c-myc exon 1. The orientation of this LTR structure was opposite to the transcriptional orientation of c-myc. The sequences at the 3' flanking side of the LTR structure were derived from a cellular DNA region which maps to the same chromosome as c-myc (chromosome 7), although to a site distant from this proto-oncogene. These findings present evidence for a homologous recombination event occurring between sequences of two proviruses integrated on the same chromosome, one of which was inserted near the c-myc proto-oncogene. The recombination product contains three copies of the MoMuLV LTR 72-base-pair direct repeat and is associated with a high level of c-myc expression. The reciprocal product of this recombination was not detected. We propose that recombination between homologous sequences may play a significant role in the generation of chromosomal rearrangements and therefore in tumor induction and progression.